2018
DOI: 10.1007/s10461-018-2191-5
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Impact of Sexual Stigma and Psychosocial Well-Being on HIV Testing: A Mixed-Methods Study Among Nigerian Men who have Sex with Men

Abstract: Although sexual stigma has been linked to decreased HIV testing among men who have sex with men (MSM), mechanisms for this association are unclear. We evaluated the role of psychosocial well-being in connecting sexual stigma and HIV testing using an explanatory sequential mixed methods analysis of 25 qualitative and 1480 quantitative interviews with MSM enrolled in a prospective cohort study in Nigeria from March/2013-February/2016. Utilizing structural equation modeling, we found a synergistic negative associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 59 publications
2
33
1
Order By: Relevance
“…In this study, more than 50% of participants had CD4 counts < 200 cells/mm 3 at entry into care. This may be related to patient-level factors such as lack of awareness of their HIV status or barriers to accessing care such as stigma [ 27 , 28 ], high costs or distance from clinics [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, more than 50% of participants had CD4 counts < 200 cells/mm 3 at entry into care. This may be related to patient-level factors such as lack of awareness of their HIV status or barriers to accessing care such as stigma [ 27 , 28 ], high costs or distance from clinics [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found the onefactor measurement of depressive symptoms to be parsimonious, providing more evidence that the CESD-R might be a reliable scale to measure depressive symptoms among Nigerian GBMSM. This is especially relevant since previous studies have found high prevalence of depressive symptoms among Nigerian GBMSM [9,10].…”
Section: Discussionmentioning
confidence: 89%
“…The minority stress model posits that the prejudice, discrimination, and stigma experienced by sexual and gender minority individuals-as a result of sexual or gender identity-contributes to higher levels of stress, which may lead to mental health problems [6] and sexual risk behaviors [7,8].Prior studies have found high levels of mental health problems (i.e. depression, anxiety, suicide ideation, and post-traumatic stress disorder (PTSD)) among Nigerian GBMSM [9,10]. Consequently, it is important to explore these topics, especially considering the vulnerable and hostile situations Nigerian GBMSM are constantly confronted with.…”
Section: Introductionmentioning
confidence: 99%
“…We found the one-factor measurement of depressive symptoms to be parsimonious, providing more evidence that the CESD-R might be a reliable scale to measure depressive symptoms among Nigerian GBMSM. This is especially relevant since previous studies have found high prevalence of depressive symptoms among Nigerian GBMSM [9,10]. Similar to the CESD-R, the MSPSS had sound psychometric properties, which suggests its' potential to accurately measure perceived social support from three distinct sources-family, friends, and significant otheramong Nigerian GBMSM.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies have found high levels of mental health problems (i.e. depression, anxiety, suicide ideation, and post-traumatic stress disorder (PTSD)) among Nigerian GBMSM [9,10]. Consequently, it is important to explore these topics, especially considering the vulnerable and hostile situations Nigerian GBMSM are constantly confronted with.…”
Section: Introductionmentioning
confidence: 99%